Impact of Digital Communication Technology on Personalization, Perception and Usage of Space - Yilwa, Joyce Lamoltongu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
This study intends to consider human behaviors in interior spaces and the possible effect digital gadgets might have on such behaviors. Human behavior in interior spaces is not a new area of study. Various researchers in the field of human behavior such as Irwin Altman and Edward T. Hall assert that humans generally exhibit certain behaviors in interior environments. These behaviors have been identified as follows: territoriality, privacy, crowding, personal space and personalization of space. These behaviors are exhibited by people as a means of a means of regulating interactions with others and also as a way of exercising conrol over what they feel belongs to them. Digital technology is a phenomenon of this present era which has permeated virtually all aspects of human life. Computers and cell phones are popular forms of this type of technology and their importance has arisen over the years due to the fact that they are able to transmit voices and information at record speeds. These new media technologies have been so inserted into man’s daily existence that they have become an intricate part of human existence today (Church et al, 2010). The use of cell phones and computers is causing great changes in many aspects of human life today. This effect is seen in reduced social relationships between people and even between people and the environment. It is not uncommon to see young people so engrossed in their cell phones that they become oblivious to what is happening around them. This clearly suggests that digital technology is gradually occupying the larger part of the average young person’s life, time and is affecting their relationships with other people and even with their immediate environment. The aim of this research is to examine if digital communication gadgets are having any effect on human relationships with and in spatial environments. Specific attention is given to perception of space, personalization of space and privacy. The Nigerian students of Eastern Mediterranean University who reside in dormitories on campus are used for case study. Data is obtained using three methods: surveys (questionnaires), interviews and personal observations and subsequently analyzed and evaluated with descriptive statistics and qualitative description. This study has various implications for society and these are discussed at the conclusion of the thesis. Several recommendations for further study have also been proffered. Keywords: Spatial Environments, Space Personalization, Perception of Space, Privacy, Digital Communication Technology

ÖZ: Bu çalışma, iç mekanlarda insan davranışlarını ve dijital araçların bu davranışların üstündeki olası etkilerini araştırmaya hedefler. İç mekanda insan davranışı yeni bir konu değildir. Irwin Altman ve Edward T. Hall gibi bu alanda çalışan farklı araştırmacılar insanların iç mekanda belli davranışlar sergilediklerini ileri sürmüşlerdir. Bu davranışlar, bölgesellik, mahremiyet, kalabalık duygusu, kişisel alan ve kişiselleştirme olarak tanımlanmıştır. Bu davranışlar insanlar tarafından başkalarıyla etkileşimlerini düzenlemek ve ait olduklarını kontrol etme araçları olarak kullanılır. Dijital teknoloji, fiilen insan hayatının tüm yönlerine nüfuz eden, günümüzün bir olgusudur. Bilgisayarlar ve cep telefonları, bilgileri rekor hızla iletebildikleri gerçeğine dayanarak, önemi yıllar içinde artmış olan bu teknolojinin popüler çeşitleridir. Bu medya teknolojileri öylesine insanın gündelik hayatına girmiştir ki günümüzün insan varlığının girift bir parçası olmuşlardır (Church et al, 2010). Günümüzde cep telefonları ve bilgisayarlar insan hayatının birçok yönünde büyük değişikliklere yol açmıştır. Bunun etkileri, insanlar arasındaki sosyal ilişkilerin ve hatta insanlar ile çevreleri arasındaki ilişkilerin azalmasında görülmektedir. Cep telefonlarına dalmaları yüzünden etraflarında ne olduğunun farkında olmayan gençleri görmek artık sıra dışı bir olay değildir. Bu, dijital teknolojinin genç insanların hayatlarının ve zamanlarının gittikçe daha büyük bir kısmını işgal ettiğini ve yakın çevreleri ile olan ilişkilerini etkilediğini göstermektedir. Bu araştırmanın amacı, dijital iletişim araçlarının mekanda insan davranışları üzerinde bir etkisi olup olmadığını bulmaktır. Bu kapsamda araştırmada mekan algılaması, mekanın kişiselleştirilmesi ve kişiselleştirme ile ilişkin olan mahremiyet ve kişisel mekan kavramları da ele alınmıştır. Doğu Akdeniz Üniversitesinin yerleşkesinde bulunan yurtlarda yaşayan Nijeryalı öğrenciler alan çalışması için seçilmiştir. Araştırma döneleri anket, görüşme, ve kişisel gözlem kullanarak elde edilmiş, analiz edilmiş ve tanımlayıcı istatistikler ve nitel tanımlar ile değerlendirilmiştir. Bu çalışmanın toplum için birçok yararı vardır. Bunlar araştırmanın sonuç bölümünde tartışılacaktır. Ayrıca ileri çalışmaları için birkaç öneri sunulmuştur. Anahtar Kelimeler: Mekansal Çevre, Mekan kişiselleştirme, Mekan algısı, Mahremiyet, Dijital İletişim Teknolojisi
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2017. Supervisor: Assist. Prof. Dr. Guita Farivarsadri.
Keywords: Architecture; Space Architecture; Spatial Environments; Space Personalization; Perception of Space; Privacy; Digital Communication Technology